2016
DOI: 10.1007/s10067-016-3231-z
|View full text |Cite
|
Sign up to set email alerts
|

Ankylosing spondylitis diagnosis in US patients with back pain: identifying providers involved and factors associated with rheumatology referral delay

Abstract: This study aimed to identify providers involved in diagnosing ankylosing spondylitis (AS) following back pain diagnosis in the USA and to identify factors leading to the delay in rheumatology referrals. The Truven Health MarketScan® US Commercial Database was searched for patients aged 18–64 years with back pain diagnosis in a non-rheumatology setting followed by AS diagnosis in any setting during January 2000–December 2012. Patients with a rheumatologist visit on or before AS diagnosis were considered referre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 24 publications
0
94
0
1
Order By: Relevance
“…Underrepresentation of axSpA in US rheumatology practices raises an important question: Where are these patients, and who is managing them? A retrospective analysis of data from 2000 to 2012 showed that only 37% of patients with AS were diagnosed by a rheumatologist [26]. The remaining 63% of patients were diagnosed by other providers, such as practitioners in primary care (26%), chiropractic/physical therapy (7%), orthopedic surgery (4%), pain clinics (4%), acute care (3%), and other settings (19%) [26].…”
Section: Us Prevalence Of Axspamentioning
confidence: 99%
“…Underrepresentation of axSpA in US rheumatology practices raises an important question: Where are these patients, and who is managing them? A retrospective analysis of data from 2000 to 2012 showed that only 37% of patients with AS were diagnosed by a rheumatologist [26]. The remaining 63% of patients were diagnosed by other providers, such as practitioners in primary care (26%), chiropractic/physical therapy (7%), orthopedic surgery (4%), pain clinics (4%), acute care (3%), and other settings (19%) [26].…”
Section: Us Prevalence Of Axspamentioning
confidence: 99%
“…Additionally, ASAS-endorsed recommendations have been developed to aid the early referral of patients with a high suspicion of AxSpA to rheumatologists [22], which is often the rate-limiting step in timely diagnosis. One study found a median delay from first record of back pain (in a non-rheumatology setting) to referral to a rheumatologist of about 10 months; however, the time to AS diagnosis following referral was only 1 month [33].…”
Section: Reducing Time To Diagnosismentioning
confidence: 99%
“…AS is a chronic inflammatory disease and primarily affects the spinal joints. 54 Recent line of evidence has implicated the role of non-HLA genes, as well as HLA-B27 gene, in AS etiology. [55][56][57] It has been demonstrated that KIRs and their HLA ligands are involved in AS etiopathogenesis.…”
Section: Discussionmentioning
confidence: 99%